2018
DOI: 10.1071/cp17348
|View full text |Cite
|
Sign up to set email alerts
|

Grain-yield stability among tropical maize hybrids derived from doubled-haploid inbred lines under random drought stress and optimum moisture conditions

Abstract: Drought is a devastating environmental stress in agriculture and hence a common target of plant breeding. A review of breeding progress on drought tolerance shows that, to a certain extent, selection for high yield in stress-free conditions indirectly improves yield in water-limiting conditions. The objectives of this study were to (i) assess the genotype × environment (GE) interaction for grain yield (GY) and other agronomic traits for maize (Zea mays L.) across East African agro-ecologies; and (ii) evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
(47 reference statements)
3
7
0
Order By: Relevance
“…Results revealed variation in magnitude of variances for GY with environment that accounted for the largest proportion followed by genotype, and genotype × environment interactions. The results are similar to those reported by Setimela et al (2010 , 2007) , Beyene et al (2011) , Makumbi et al (2015) and Sserumaga et al (2018 , 2016) . The large environmental variance indicates that the testing sites were highly variable from one environment to another.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Results revealed variation in magnitude of variances for GY with environment that accounted for the largest proportion followed by genotype, and genotype × environment interactions. The results are similar to those reported by Setimela et al (2010 , 2007) , Beyene et al (2011) , Makumbi et al (2015) and Sserumaga et al (2018 , 2016) . The large environmental variance indicates that the testing sites were highly variable from one environment to another.…”
Section: Discussionsupporting
confidence: 92%
“…The implication of significant genotype × environment interaction implies that there is differential hybrid performance across variable conditions. Similar observations were reported by several authors ( Beyene et al, 2013 ; Ertiro et al, 2017 ; Sserumaga et al, 2018 , 2016 ) who studied about adaptability and performance of maize hybrids under different stress conditions in eastern Africa.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Since 2013, CIMMYT has developed more than 200,000 maize DH lines from diverse source populations and successfully identified maize DH lines with superior characteristics for use in breeding pipelines in SSA, Latin America, and Asia. These DH lines have superior per se performance (Worku et al 2016 ; Beyene et al 2017a ), good combining ability for stress tolerance (Beyene et al 2013 , 2017a , Erito et al 2017; Sserumaga et al 2018 ), and tolerance/resistance to various diseases (Beyene et al 2017b ).…”
Section: Increasing Genetic Gain In the Stress-prone Tropical Environmentioning
confidence: 99%
“…This observation was supported earlier by Johnson and Frey (1967) who reported that varieties selected directly from stressed conditions exhibit a low genotype × environment (G × E) interaction compared to those selected under optimal conditions. However, some studies show that selection under optimal environments also improves grain yield under drought conditions to a limited extent (Araus et al, 2002;Cattivelli et al, 2008;Sserumaga et al, 2018). Mohammadi and Amri (2011) indicate that grain yield improvement may be attained by either selection in low input and stressed environments or by selection in non-stressed conditions followed by selection under stressed conditions.…”
Section: Targets For Breeding Drought-tolerant Wheat Selection Enviromentioning
confidence: 99%